2020
DOI: 10.1029/2020gb006677
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Fire, Vegetation, and Climate in Tropical Ecosystems: A Multiproxy Study Over the Past 22,000 Years

Abstract: Fire causes dramatic energy and matter exchanges between biosphere and atmosphere on a regional to global scale. Predicting fires, however, is hindered by the complex interplay of fire, climate, and vegetation. Paleo-fire records provide critical information beyond instrumental records that cover only the past few decades and may be used to assess the role of fire in large-scale and long-term environmental changes. Here we present a 22,000-year multiproxy record of fire regime from a sediment core retrieved of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…BA Our model results reproduce the global reduction of biomass burning at the LGM observed from ice cores and sedimentary charcoal records (Daniau et al, 2012;Harrison et al, 2022;Power et al, 2008;Rubino et al, 2016). Some studies have indicated the occurrence of high-intensity wildfires on the Palaeo-Agulhas Plain of South Africa, tropical regions, northern Australia, and central China at the LGM (Kraaij et al, 2020;Power et al, 2008;Rowe et al, 2021;Ruan et al, 2020;M. Song et al, 2023).…”
Section: Discussionsupporting
confidence: 75%
“…BA Our model results reproduce the global reduction of biomass burning at the LGM observed from ice cores and sedimentary charcoal records (Daniau et al, 2012;Harrison et al, 2022;Power et al, 2008;Rubino et al, 2016). Some studies have indicated the occurrence of high-intensity wildfires on the Palaeo-Agulhas Plain of South Africa, tropical regions, northern Australia, and central China at the LGM (Kraaij et al, 2020;Power et al, 2008;Rowe et al, 2021;Ruan et al, 2020;M. Song et al, 2023).…”
Section: Discussionsupporting
confidence: 75%
“…By contrast, charcoal particles are produced at all temperatures and thus reflects general fire frequency. This proxy is similar to PAH ratios used to determine changes in Indonesian fire regimes over the past 22,000 years 45 . For this study, samples were decarbonated by immersion in 2 M HCl for 3 h and measured for the total organic carbon abundance (TOC).…”
Section: Methodsmentioning
confidence: 94%
“…Comparative studies on soils and aerosols have shown that the most commonly used extraction protocol for levoglucosan using MeOH or DCM:MeOH mixtures yielded comparable result (Cordell et al., 2014 ; Hopmans et al., 2013 ). While these comparisons were conducted on modern sample material, a study from a Pleistocene marine sediment core showed that MeOH extraction was on average five times more efficient than DCM:MeOH 9:1 (Ruan et al., 2020 ). While all modern marine and riverine sediment data sets reported here were produced using DCM: MeOH mixtures, the discussed Holocene lacustrine sediment records were produced using MeOH as extraction solvent (Elias et al., 2001 ; Hunsinger et al., 2008 ; Myers‐Pigg et al., 2017 ; Schreuder et al., 2018 ; Schupbach et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%